Physics essentials for dummies - Holzner, Steven; Wohns, Daniel (For dummies., 2010)
From the Publisher: For students who just need to know the vital concepts of physics, whether as a refresher, for exam prep, or as a reference, Physics Essentials For Dummies is a must-have guide. Free of ramp-up and ancillary material, Physics Essentials For Dummies contains content focused on key topics only. It provides discrete explanations of critical concepts taught in an introductory physics course, from force and motion to momentum and kinetics. This guide is also a perfect reference for parents who need to review critical physics concepts as they help high school students with homework assignments, as well as for adult learners headed back to the classroom who just need a refresher of the core conce.